2003
DOI: 10.1074/jbc.m211641200
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Polymerase-1 Is a Positive Regulator of the p53-mediated G1 Arrest Response following Ionizing Radiation

Abstract: The p53 tumor suppressor protein plays a critical role in the cellular response to DNA damage leading to cell cycle arrest or apoptosis depending on cell type, culture conditions, and the extent of DNA damage. Loss of the p53-dependent DNA damage response can lead to genomic instability and the survival of cells carrying mutations and carcinogenic lesions thereby contributing to malignancy (1). DNA strand breaks produced by ionizing radiation (IR) 1 or by DNA repair intermediates following treatment with UV ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 47 publications
5
72
0
Order By: Relevance
“…As it has also been shown that PARP-1 interacts with p53 and positively regulates p53 activity (Wieler et al, 2003), we then examined the level of PARP-1 and its degradation product p89 in BubR1 þ /À MEFs before and after doxorubicin treatment. There was a low basal level of PARP-1 in BubR1 þ /À MEFs before initiation of doxorubicin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…As it has also been shown that PARP-1 interacts with p53 and positively regulates p53 activity (Wieler et al, 2003), we then examined the level of PARP-1 and its degradation product p89 in BubR1 þ /À MEFs before and after doxorubicin treatment. There was a low basal level of PARP-1 in BubR1 þ /À MEFs before initiation of doxorubicin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies involving transgenic mouse models are needed to determine the underlying mechanisms. Human PARP1 plays a crucial role in the BER pathway (Dantzer et al, 1999;Wieler et al, 2003). PARP1 is constitutively expressed, and its catalytic activity is strongly stimulated in response to single-or double-stranded DNA breaks (Lindahl et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…97 Furthermore, constitutive levels of p53 were down in PARPÀ/À mutant mice, DNA damage-induced stabilization of p53 was also defective 98 and inhibition of PARP activity delayed and attenuated the induction of the p53-responsive genes, p21 and MDM2. 99 Thus, PARP joins a long list of proteins that influence the stabilization and/or activation of p53.It remains unclear how this is achieved but its capacity to bind p53 may be pertinent.…”
Section: Multiple Proteins Influence the Stabilization And Activationmentioning
confidence: 99%